DIGITALISASI MOBILE BANKING BSI DI ERA DIGITAL : STRATEGI, TANTANGAN, DAN PELUANG - Zulkipli, Zulkipli; Mas’ud, Riduan; Aziz, Ahmad Amir; Azkar, Muh.; Wajdi, Farid (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
This study aims to analyze the digitalization strategies of mobile banking services implemented by Bank Syariah Indonesia (BSI) and to identify the challenges and opportunities arising from the digital transformation process grounded in Sharia principles. This research employs a qualitative method with a literature review approach, drawing from scholarly journals, reputable articles, and official documents from relevant financial institutions. The findings reveal that BSI adopts three primary strategies in its digitalization efforts: (1) post-merger technology integration, (2) service innovation through the BSI Mobile application, and (3) internal business process transformation. However, several challenges persist, including low levels of digital literacy among the population, limited infrastructure in frontier, outermost, and underdeveloped (3T) regions, competition with conventional digital banks, and the need to ensure Sharia compliance in technological features. On the other hand, BSI holds strategic opportunities to enhance financial inclusion, target the millennial demographic, and actively contribute to the development of a halal digital economic ecosystem through the innovation of Sharia-compliant financial products. With proper management, this digital transformation has the potential to position BSI as a pioneering, adaptive, competitive, and sustainable digital Islamic bank.